2017
DOI: 10.1111/zph.12426
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review: Impact of point sources on antibiotic‐resistant bacteria in the natural environment

Abstract: SummaryPoint sources such as wastewater treatment plants and agricultural facilities may have a role in the dissemination of antibiotic-resistant bacteria (ARB) and antibiotic resistance genes (ARG). To analyse the evidence for increases in ARB in the natural environment associated with these point sources of ARB and ARG, we conducted a systematic review. We evaluated 5,247 records retrieved through database searches, including both studies that ascertained ARG and ARB outcomes. All studies were subjected to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 72 publications
0
28
0
Order By: Relevance
“…Heavy metals and disinfectants with antibacterial properties also favor the bacterial resistance present in these waters [100]. Surface waters are the main recipient of treated and untreated wastewaters favoring the dissemination of resistance genes in microbial communities via water, land or even through wildlife [102]. Nonetheless, only a few studies have been carried out in Europe in order to determine the presence of S. aureus, its antimicrobial resistance profiles, and its genetic lineages in surface waters [56,[103][104][105].…”
Section: Antibiotic Resistance In the Environmentmentioning
confidence: 99%
“…Heavy metals and disinfectants with antibacterial properties also favor the bacterial resistance present in these waters [100]. Surface waters are the main recipient of treated and untreated wastewaters favoring the dissemination of resistance genes in microbial communities via water, land or even through wildlife [102]. Nonetheless, only a few studies have been carried out in Europe in order to determine the presence of S. aureus, its antimicrobial resistance profiles, and its genetic lineages in surface waters [56,[103][104][105].…”
Section: Antibiotic Resistance In the Environmentmentioning
confidence: 99%
“…This argues for greater unification among methods and study designs to provide less ambiguous results. A recent review concluded that there was a broad lack of quantitative causal research that associates AMR sources and increases in environmental ARB, suggesting that improved study design, greater consideration of a priori bias, and standardization of analytical tools are important to understanding better how ARBs in the environment affect human and animal health …”
Section: Complexity Of Antimicrobial Resistance Across Domesticated Amentioning
confidence: 99%
“…A third objective of this systematic review was to provide an overview of available evidence on what happens in the environment when it is exposed to different sources of ATBR. A systematic review has been published during the course of our work on impacts of point sources on ARB in natural environment [21]. Considering that similar articles were retrieved by our searches, we chose to include them in the evidence map.…”
Section: Objectives Of the Reviewmentioning
confidence: 99%